Blood serotonin levels in postmenopausal women: Effects of age and serum oestradiol levels - Gonzales G.F. (1993)
This study investigated the effect of ageing and reduction in ovarian function on whole blood serotonin levels and the effect of the oestrogen replacement in postmenopausal women on blood serotonin levels. Amenorrbeic, natural postmenopausal and ovariectomised women had lower blood serotonin levels than regularly menstruating women. Blood serotonin levels increased after oestrogen replacement in postmenopausal women to values similar to those observed in regularly menstruating women. In ovariec-tomised women, the blood serotonin levels were inversely correlated with age (P < 0.01). In women with different serum oestradiol levels ranging 30–1335 pg/ml, a direct relationship was observed between serum oestradiol levels and whole blood serotonin levels (P < 0.001). It was concluded that whole blood serotonin concentration is reduced during menopause by suppression of ovarian function but may also be an effect of ageing.